Evaluation of reclaimed asphalt pavement binder stiffness without extraction and recovery - Ma, Tao; Huang, Xiao-ming; Hussain, U. B. (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2011)
A new testing procedure to estimate the low-temperature stiffness of the reclaimed asphalt pavement (RAP) binder was developed. In the testing procedure, the Superpave™ Bending Beam Rheometer (BBR) with special modifications and binder blending charts by Asphalt Institute were utilized. Modifications involved the development of a new kind of sample mold and different testing parameters were made to BBR testing procedure to capture the rheological properties of bitumen mortars produced by mixing fresh binder with fine RAP materials or RAP aggregate. The stiffness relationship between binder and bitumen mortar was established based on the BBR test results. The blended binder stiffness in bitumen RAP mortar was estimated from the RAP mortar stiffness based on the binder-mortar relationship. And finally, the RAP binder stiffness was estimated from the blended binder and fresh binder stiffness based on the blending charts by Asphalt Institute. The results indicate that the new procedure can capture the rheological properties of bitumen mortar and can be used to estimate the low temperature stiffness of RAP binder without binder extraction and/or any chemical treatments.